2016
DOI: 10.1016/j.cub.2016.04.035
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Working Memory in Humans Depends on Theta and High Gamma Synchronization in the Prefrontal Cortex

Abstract: Previous, albeit correlative, findings have shown that the neural mechanisms underlying working memory critically require cross-structural and cross-frequency coupling mechanisms between theta and gamma neural oscillations. However, the direct causality between cross-frequency coupling and working memory performance remains to be demonstrated. Here we externally modulated the interaction of theta and gamma rhythms in the prefrontal cortex using novel cross-frequency protocols of transcranial alternating curren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
268
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 289 publications
(283 citation statements)
references
References 48 publications
14
268
0
1
Order By: Relevance
“…Although this shows that tDCS interacts with the neural mechanisms associated with WM, future studies should carefully consider the biological processes they aim to target, as different tES modalities impact brain excitability to different degrees (Inukai et al, 2016). Furthermore, a recent study elegantly demonstrated that WM performance is very sensitive to the external stimulation parameters (Alekseichuk et al, 2016). A study comparing different tES modalities could help answer this question.…”
Section: Discussionmentioning
confidence: 99%
“…Although this shows that tDCS interacts with the neural mechanisms associated with WM, future studies should carefully consider the biological processes they aim to target, as different tES modalities impact brain excitability to different degrees (Inukai et al, 2016). Furthermore, a recent study elegantly demonstrated that WM performance is very sensitive to the external stimulation parameters (Alekseichuk et al, 2016). A study comparing different tES modalities could help answer this question.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, while a part of the electric field focused over the targeted hand area of the M1, the electric field spread further towards the contralateral electrode and covered part of the ipsi- and contralateral supplementary motor cortex. To increase the focality of the electric field over the M1 region one possibility would be to use the high definition electrode montage as shown by Datta et al (2009) and Alekseichuk et al (2016). It is known from other studies that when increasing stimulation intensities from a subthreshold level, at first inhibition occurs and then eventually, after passing a transition zone without a stimulation effect, excitation is induced (Moliadze et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…We applied electric stimulation in a TBS mode using 5 kHz high-frequency tACS. At frequencies below 1 kHz, tACS is believed to entrain or synchronize neuronal oscillations with effects on excitability but also behavioral aspects such as learning (Alekseichuk et al, 2016). If applied in the kHz range, tACS is thought to preferentially modulate the membrane excitability of neurons (Antal and Paulus, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The feasibility of this approach has recently been shown for TACS-TMS over motor cortex (Raco et al, 2016). Others have combined two TACS waveforms (Alekseichuk et al, 2016) to emulate the circuit motif of cross-frequency phase-power couplings, reported in many EEG/MEG-studies (see section 2 above). To this end, Alekseichuk et al (2016) applied TACS over frontal areas in a cross-frequency regime, while participants were performing a working memory task.…”
Section: What Is the Empirical Support That Tuning Ntbs To Oscillamentioning
confidence: 99%